Naturalization and Immigrants' Health - Ainoa Aparicio Fenoll (Institute of Labor Economics (IZA), 2022)
The "healthy immigrant effect" refers to the well-documented fact that immigrants are healthier than natives upon arrival, but their health level converges to that of natives over time. Unfortunately, little is known about whether environmental, institutional, or selective return migration mechanisms are behind the convergence. In this paper, I test whether immigrants' naturalization influences health convergence speed. Using restricted-access Spanish health data from the National and European Health Surveys, I estimate the impact of naturalization on health by exploiting that naturalization is possible after two years of residence for Latinoamerican immigrants and after ten years for all other immigrants. I find that naturalization worsens immigrants' health and thus accelerates the speed of convergence to natives' health. In particular, naturalization increases the propensity to suffer from varicose veins, cervical problems, lower back pain, constipation, depression, and anxiety. Changes in dietary habits and increases in employment are potential mechanisms behind these effects.
Keywords: J15; J61; I14; 330; naturalization; immigrants' health; healthy immigrant effect